2002
DOI: 10.1179/joc.2002.14.1.47
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Studies on Synergism Between Aminoglycosides and the Antimicrobial Antiinflammatory Agent Diclofenac Sodium

Abstract: The antiinflammatory agent diclofenac sodium (Dc) exhibited remarkable antibacterial effects both in vitro and in vivo. Fifteen different bacteria sensitive to Dc as well as to a number of common antibiotics were tested for synergistic effects in vitro. Disc diffusion test with Dc and aminoglycosides assessed by stringent computation showed clear-cut synergism. Synergism between Dc and streptomycin (Sm) was found to be statistically significant (p < or = 0.01) when compared with their individual effects. By th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 3 publications
2
27
0
Order By: Relevance
“…Table 5 shows that of the 10 animals in the untreated group, all developed minute tubercles in the liver, 5 in the spleen, 5 in the lungs and 9 in the peritoneum and intestines; microscopic necrosis suggestive of caseation was found in the liver of 3 animals and in the spleen, peritoneum and intestines each in one animal. Smears for acid-fast bacilli by Z-N stain, from centrifuged deposits (for 100 fields) of tissue homogenates, effects of Dc and Sm, as well as Dc and the non-antibiotic trifluoperazine on Gram positive and Gram negative bacteria provided significant synergism both through in vitro and in vivo experiments (4,11). In the present study, Dc has shown a remarkable antitubercular activity against a number of mycobacteria.…”
Section: Synergism Between DC and Sm By Disc Diffusion Testsmentioning
confidence: 75%
“…Table 5 shows that of the 10 animals in the untreated group, all developed minute tubercles in the liver, 5 in the spleen, 5 in the lungs and 9 in the peritoneum and intestines; microscopic necrosis suggestive of caseation was found in the liver of 3 animals and in the spleen, peritoneum and intestines each in one animal. Smears for acid-fast bacilli by Z-N stain, from centrifuged deposits (for 100 fields) of tissue homogenates, effects of Dc and Sm, as well as Dc and the non-antibiotic trifluoperazine on Gram positive and Gram negative bacteria provided significant synergism both through in vitro and in vivo experiments (4,11). In the present study, Dc has shown a remarkable antitubercular activity against a number of mycobacteria.…”
Section: Synergism Between DC and Sm By Disc Diffusion Testsmentioning
confidence: 75%
“…Nevertheless, although many new anti-infective compounds are reported in the literature, it is expected that the appearance of mutations and acquisition of drug-resistant plasmids will restrict their usage for therapy of infections [6,7]. However, several studies have revealed that significant antimicrobial actions are present in a large number of pharmacologically diverse categories of compounds designated as "non-antibiotics" [8][9][10][11][12][13][14][15][16][17][18][19][20]. Moreover, some of these "non-antibiotics" act synergistically with conventional antibiotics rendering initially antibioticresistant bacteria susceptible [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the diameters of inhibition zones produced due to individual and mutual effects of two drugs were recorded on the same plate. The mutual influence/interference encountered when two drugs were used in combination was assessed as follows 15) : (i) indifference, when both the zones of inhibition remained unaffected; (ii) antagonism, when the zones of inhibition receded and assumed kidney shape; (iii) synergism, in which there was enlargement of zones. The statistical evaluation of the increase in surface area (pr 2 ) of a zone, if any, due to a combination of effects was done by the c 2 test for its level of significance.…”
Section: Bacteriamentioning
confidence: 99%
“…14) Many of these non-antibiotic agents have further shown remarkable synergistic action with several antibiotics and other non-antibiotics. 15,16) The antianginal and coronary vasodilator oxyfedrine HCl (Oxy) was previously reported to be a non-antibiotic agent that demonstrated significant antimicrobial action. 17) This drug could inhibit bacteria in the following order: Staphylococcus aureus, vibrios, Bacillus spp., Shigella spp., Salmonella spp., Escherichia coli, Klebsiella spp.…”
mentioning
confidence: 99%